RADICL CTF: Low-Cost CTF Platform for Industrial Control Systems Education (Journal of The Colloquium for Information Systems Security Education, 2023)
To address the nationwide workforce shortage of skilled and educated cyber-informed engineers, we must develop low-cost and highly effective resources for industrial control systems education and training. College curricula in technology management, cybersecurity, and computer science aim to build students’ computational and adversarial thinking abilities but are often done only through theory and abstracted concepts [1]. To better a student’s understanding of industrial control system applications, post-secondary institutions can use gamification to increase student interest through an interactive, user-friendly, hands-on experience. RADICL CTF can provide post-secondary institutions with new opportunities for low-cost, guided exercises for industrial control system (ICS) education to help students master adversarial thinking. Based on an extension to picoCTF, RADICL CTF is a platform for students to design, implement and evaluate exercises that test their understanding of core concepts in industrial control systems cybersecurity, answering the need for more interactive education methods. The main contributions of this paper are the improvement of the cyber-security curriculum through extending the picoCTF platform to promote the gamification of industrial control system concepts with consideration to the Purdue Reference Architecture.
Keywords: Cybersecurity; Capture the Flag; Gamification; Cyber-Physical Systems; Industrial Control System; Education; RADICL; picoCTF